Analysis of the changing trend of economic burden of patients with chronic diseases under the Integrated Medical and Health Service System - Xuedan Pei; Bing Wang; Xiaohong Yang; Wenming Feng; Yanqiu Sun; Hao Wang; Li Gao; Yinuo Gu; Yening Bei (BMC, 2023)
Abstract Background Integrating medical resources is one of the explorations of medical mechanism reform to meet the needs of whole-cycle health management and is an important initiative in the current round of China's healthcare system reform. 2015 saw the construction of county medical communities to promote the balanced layout of medical resources, which opened a new exploration of the construction of an integrated healthcare service system in China. 2017 saw the promotion of the pilot construction of compact county medical communities in Zhejiang Province, China. Objective From the perspective of alleviating the financial burden on those in need of health services, the characteristics of chronic disease patients' access to health care and the composition and changing curve of the medical cost burden are analyzed to provide a basis for the construction path of an integrated health care service system. Methods A retrospective cohort study was conducted to select 5739 permanent residents who met the inclusion and exclusion criteria in Z town, H city, Zhejiang province. This population's health insurance utilization data from 2015 to 2018 were retrieved, and their average annual costs, cost composition, and health insurance payments were analyzed. Results The average annual growth rates of medical insurance and out-of-pocket costs before and after the implementation of the Medical Community were 12.85% and 9.72%, respectively. The increase narrowed significantly after the construction of the Medical Community, with the ringgit growth rate dropping to 2.73% in 2018. The top three medical expenses that accounted for the highest percentage were drug, consultation, and treatment fees. The frequency of visits to primary health care consulting hospitals has increased yearly. Conclusions By implementing various measures to strengthen the grassroots level, patients' choice of primary care has increased year by year in the early stages of the construction of the Medical Community. From the perspective of cost control, strengthening the regulation of drugs and tests and restricting the use of high-value consumables can further reduce medical costs and ease their financial burden.